Amor - Gámez Rodríguez, Javier (Editorial Unimagdalena, 2025)
Love, a kaleidoscope of emotions woven by the pen of Javier Gámez, unfolds in a journey through the magical landscapes of Salónica the warm breeze of Santa Marta, and the charming streets of Medellín. In Salonica, among the walls that keep the secrets of ancient loves, Gámez immerses us in the nostalgia of an empty castle and the dance between gods, where the ruins and the coffee become witnesses of loves that reinvent themselves at every step. Santa Marta, with its vast universe, reveals the skin of stars and the fury of the tenant, while interspecies communication becomes an underwater lament. In the timetable of his body, the poet dives into the depths of the soul, facing storms and lunar liquor. Medellin, the city of being-we-ness and thalassophobia, stands like a volcano that burns, unleashing a violent tempest. Between memories and the monster that dwells in the closet, Gámez invites us to explore the richness of life, where each word is a drop of rain in the vast ocean of existence.